Heidegger's ontology of events - Bahoh, James (New perspectives in ontology., 2020)
James Bahoh proposes a new methodology for explaining Heidegger's philosophy that solves a set of interpretive problems in his difficult later work and led to substantial inconsistencies in the scholarship. Bahoh reconstructs Heidegger's concept of event in relation to his theories of history, truth, difference, ground and time-space.